Yeast m6 A methylated mRNAs are enriched on translating ribosomes during meiosis, and under rapamycin treatment - Bodi, Zsuzsanna; Bottley, Andrew; Archer, Nathan; May, Sean; Fray, Rupert G. (Public Library of Science, 2015)
Interest in mRNA methylation has exploded in recent years. The sudden interest in a 40 year old discovery was due in part to the finding of FTO’s (Fat Mass Obesity) N6-methyladenosine (m6 A) deaminase activity, thus suggesting a link between obesity-associated diseases and the presence of m6 A in mRNA. Another catalyst of the sudden rise in mRNA methylation research was the release of mRNA methylomes for human, mouse and Saccharomyces cerevisiae. However, the molecular function, or functions of this mRNA ‘epimark’ remain to be discovered. There is supportive evidence that m6 A could be a mark for mRNA degradation due to its binding to YTH domain proteins, and consequently being chaperoned to P bodies. Nonetheless, only a subpopulation of the methylome was found binding to YTHDF2 in HeLa cells.The model organism Saccharomyces cerevisiae, has only one YTH domain protein (Pho92, Mrb1), which targets PHO4 transcripts for degradation under phosphate starvation. However, mRNA methylation is only found under meiosis inducing conditions, and PHO4 transcripts are apparently non-methylated. In this paper we set out to investigate if m6 A could function alternatively to being a degradation mark in S. cerevisiae; we also sought to test whether it can be induced under non-standard sporulation conditions. We find a positive association between the presence of m6 A and message translatability. We also find m6 A induction following prolonged rapamycin treatment.